'You can't be green if you're in the red': Local discourses on the production-biodiversity intersection in a mixed farming area in south-eastern Australia. (October 2022) - Schaal, Tamara; Jacobs, Annie; Leventon, Julia; Scheele, Ben C.; Lindenmayer, David; Hanspach, Jan
Abstract: Limiting biodiversity loss is a global challenge, especially in areas where biodiversity conservation conflicts with intensifying agricultural production. The different views and preferences about how to protect biodiversity, and why it is valuable, make concerted action to improve conservation outcomes difficult. Exploring different discourses that represent shared understandings of an issue or a topic can help to understand this plurality. We focused on a mixed farming area in south-eastern Australia where intensive agricultural production is linked to an ongoing loss of biodiversity. Using the Q-methodology, we conducted 94 interviews with people who may influence biodiversity outcomes in farming landscapes to explore shared understandings of the farming-biodiversity intersection. We also sought to understand how such discourses relate to perceptions of biodiversity in agricultural contexts and if they are associated with particular stakeholder groups. We identify four discourses on the relationship between farming and biodiversity, the farmers' role and responsibility for biodiversity, and the preferred approaches to improve biodiversity outcomes. Our findings highlight how perceptions of biodiversity by agricultural stakeholders varied substantially between discourses, but that discourses were not significantly associated with stakeholder group. We discuss our findings in the context of policy development and broader governance. We consider how a balanced mix of policy instruments, including market and community-based instruments, can better engage with contrasting understandings of the production-biodiversity intersection. To improve biodiversity outcomes, it is necessary to integrate a plurality of biodiversity values and ensure a broad and balanced set of policy instruments that supports land managers as stewards of the land. Highlights: Used Q-methodology to explore shared understandings about biodiversity in farming. Identified four different discourses about the biodiversity-farming intersection. Underlying polarity between agroecological and pro-production perspectives. Discourses were not associated with stakeholder groups.